Reintroductions of native plant species to the United Kingdom. Issue 1 (3rd April 2017) - Bird, S. A.; Esseen, P. J.; Hewitt, R.
Abstract : Zoos can play a key role in the conservation of native plant species, and projects concerning the reintroduction and reinforcement of local plant populations are potentially an ideal way to involve visitors and local communities in practical conservation. However, such projects need to be clearly thought through and designed correctly from the start. Knowledge and understanding of relevant International Union for Conservation of Nature guidelines are important to ensure that reintroductions are ethical and sustainable. Many zoological institutions tend not to get involved in such local projects, favouring more exotic and attention‐grabbing conservation programmes. Chester Zoo, UK, has engaged with partners and worked with various native plant species, predominantly in Cheshire and North Wales, including Black poplar Populusnigra  ssp  betulifolia, Common barberry Berberis vulgaris and Common juniper Juniperus communis . There have been a number of key lessons learned, which can be applied to the design and management of future projects. Abstract : Zoos can play a key role in the conservation of native plant species, and projects concerning the reintroduction and reinforcement of local plant populations are potentially an ideal way to involve visitors and local communities in practical conservation. Such projects need to be clearly thought through and designed correctly from the start. Knowledge and understanding of relevant International Union for Conservation of Nature guidelines are important to ensure that reintroductions are ethical and sustainable. Chester Zoo, UK, has engaged with partners and worked with various species of native plants, predominantly in Cheshire and North Wales, including Black poplar Populus nigra  ssp  betulifolia, Common barberry Berberis vulgaris and Common juniper Juniperus communis . There have been a number of key lessons learned, which can be applied to the design and management of future projects.(Photo: Philip Esseen, Chester Zoo)